PENINGKATAN KECERDASAN INTERPERSONAL TENTANG SENSITIVITAS SOSIAL MELALUI METODE CONTEXTUAL TEACHING AND LEARNING (CTL) DALAM PEMBELAJARAN IPS - Wina Mustikaati; Nurdiansyah; Ela Hayati (Jurnal Binagogik, 2025)
sensitivity of the community, especially among students at the elementary education level, resulted in a decline in the social sensitivity of the community. In line with the mandate of learning in the form of competency achievement needed in the 21st century, it encourages changes in the learning process. Developing students' soft skills skills combined with CTL methods is expected to be able to answer problems that arise regarding social sensitivity among students, especially for V-grade students of Peditia Elementary School, Purwakarta Regency. The purpose of this study is that it is necessary to conduct research to measure students' level of social sensitivity through CTL learning methods.  This study uses a quantitative approach in which data collection uses instruments in the form of Likert scales to measure the level of social sensitivity of students who have previously been given treatment using CTL methods in their learning process as well as observation and documentation data carried out during practice. and post-treatment, and interviews to obtain preliminary data as a description before research is conducted. The obtained instrument data are then analyzed using descriptive statistics. Because research has not been conducted and treatment has not been conducted, the data presented is preliminary data in the form of interviews and observations that have been conducted previously. The results of this study obtained a level of social sensitivity in students before conducting CTL studies of 82% of grade VI students had a high level of social sensitivity and a level of social sensitivity and response after learning with CTL method 87% of grade V students had a level of social sensitivity It is a very high level and able to apply awareness of social sensitivity in everyday life.